Prevalence of dental anomalies in patients visiting a tertiary care hospital - Baral, Radha; Dahal, Samarika; Manandhar, Dhan Kumari; Dahal, Sirjana (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Changes in dental anatomy resulting from hereditary and environmental influences during tooth development are known as anomalies. Abnormalities in tooth number, shape, size and structure result from disturbances during different stages of tooth development. This study was conducted to assess the prevalence of dental anomalies among patients visiting a dental teaching hospital in Kathmandu.Methods: In this descriptive cross-sectional study, dental anomalies affecting tooth shape, number, and position were evaluated on digital orthopantomograms. Data was analyzed in SPSS version 24. Mean, standard deviation, frequency, and percentage were calculated for descriptive data analysis.Results: Among 200 radiographs observed, 20(10.00%) had at least one dental anomaly present. Anomaly affecting shape was observed in 9(4.50%), and anomaly affecting number in 12(6.00%). Impacted tooth was present in 150(75%). The third molar impaction was seen in 89(44.50%). Only 3(1.5%) of patients’ radiographs showed canine impaction. Five (2.5%) teeth with dilaceration and 4(2.0%) peg-shaped laterals were observed. Eight (4.0%) patients had at least one missing tooth. Paramolar, distomolar, mesiodens and multiple supernumerary teeth were present in 1(0.5%).Conclusions: The findings of this study revealed that dental anomalies were present in a small yet notable proportion in radiographs of patients visiting a dental teaching hospital. Impaction was the most prevalent anomaly affecting tooth position, present in three-fourths of the radiographs, predominantly involving third molars. Routine radiographic evaluation, particularly panoramic radiographs, should be considered in young adults to detect impaction and other anomalies at an early stage.